Simultaneous determination of phthalates, their metabolites, alkylphenols and bisphenol a using GC-MS in urine of men with fertility problems - Kranvogl, Roman (Acta chimica slovenica, 2014)
A GC-MS method was successfully applied to measure simultaneously the concentrations of endocrine disrupting compounds (5 dialkyl phthalates, 9 phthalate monoesters, 3 alkylphenols and bisphenol A) in 136 male urine samples. In the present study the method was validated and concentrations of EDCs were determined. The results were compared with results from other studies. Correlations between endocrine disrupting compounds and also correlations of endocrine disrupting compounds with two semen quality parameters are presented and evaluated. Significant positive correlations were found between almost all the endocrine disrupting compounds. The parameter sum of DEHP (SUM DEHP) was positively correlated to all the endocrine disrupting compounds but negatively to two semen quality parameters. Negative correlations between the endocrine disrupting compounds and the semen quality parameters could indicate that endocrine disrupting compounds could cause reproductive problems by decreasing the semen count and quality. This research will have helped to evaluate human exposure to endocrine disrupting compounds.
Keywords: alkylphenols; analizna kemija; bisphenol A; endocrine disrupting compounds; endokrini motilci; fertility; ftalati; human urine; kemijska analiza; phthalates; plinska kromatografija; urin